2017
DOI: 10.1371/journal.pone.0182406
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of surface roughness changes of unpolished and polished enamel following erosion

Abstract: ObjectivesTo determine if Sa roughness data from measuring one central location of unpolished and polished enamel were representative of the overall surfaces before and after erosion.MethodsTwenty human enamel sections (4x4 mm) were embedded in bis-acryl composite and randomised to either a native or polishing enamel preparation protocol. Enamel samples were subjected to an acid challenge (15 minutes 100 mL orange juice, pH 3.2, titratable acidity 41.3mmol OH/L, 62.5 rpm agitation, repeated for three cycles). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…Baseline values for natural enamel indicate a complex textured surface, which is supported by visual evidence from the confocal images, thereby the effect of roughness change value is partly determined by the baseline values and the variation within the sample micro-structure. Natural enamel became significantly smoother after erosion whilst polished enamel became rougher, following recent trends [15,24,27,33]. These differences in behaviour between the two surfaces cannot be attributed to the differences in measurement capabilities and remain true representations.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Baseline values for natural enamel indicate a complex textured surface, which is supported by visual evidence from the confocal images, thereby the effect of roughness change value is partly determined by the baseline values and the variation within the sample micro-structure. Natural enamel became significantly smoother after erosion whilst polished enamel became rougher, following recent trends [15,24,27,33]. These differences in behaviour between the two surfaces cannot be attributed to the differences in measurement capabilities and remain true representations.…”
Section: Discussionmentioning
confidence: 85%
“…This study identified that the optical measurement system could reliably identify Sa roughness changes as small as 5 nm for polished enamel and 23 nm for natural enamel. Whilst there were differences in the precision of measurement across the five measurement areas, these differences were minimal of 4 nm for polished and 16 nm for natural enamel therefore suggesting that the level of precision is within the limits of detection required for reliable measurement of 3D surface texture changes of enamel undergoing erosion [18,20,27].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations